2019
DOI: 10.1177/1533033819859413
|View full text |Cite
|
Sign up to set email alerts
|

Association of Methylenetetrahydrofolate Reductase, Vitamin D Receptor, and Interleukin-16 Gene Polymorphisms With Renal Cell Carcinoma Risk

Abstract: In this meta-analysis, we investigated the association of methylenetetrahydrofolate reductase, vitamin D receptor, and interleukin-16 gene polymorphisms with the risk of renal cell carcinoma. We searched the PubMed and Cochrane Library databases up to July 1, 2017, and included 12 eligible case–control studies in our analysis. The vitamin D receptor ApaI A allele, ApaI AA and aa genotypes, BsmI B allele, and Fok1 FF genotype were all associated with the risk of renal cell carcinoma in Asian populations. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Yang et al [19] also indicated that VDR ApaI gene mutation was associated with increased risk and susceptibility to RCC in Chinese Han population. Recently, a meta-analysis [15] obtained similar results with forementioned studies. In current study, we did not find any relationship of FokI, TaqI and BsmI with RCC risk, but we found a significant relation between ApaI and RCC risk.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Yang et al [19] also indicated that VDR ApaI gene mutation was associated with increased risk and susceptibility to RCC in Chinese Han population. Recently, a meta-analysis [15] obtained similar results with forementioned studies. In current study, we did not find any relationship of FokI, TaqI and BsmI with RCC risk, but we found a significant relation between ApaI and RCC risk.…”
Section: Discussionsupporting
confidence: 72%
“…Such as FokI and BsmI, as defined by the endonucleases FokI and BsmI, respectively, have been most frequently studied in the previous studies. Previously, several studies [13][14][15][16] have been performed to evaluate the association between VDR polymorphisms and RCC risk in different populations, including several meta-analysis studies; however, the results of these studies were conflict. In addition, previous studies have shown that the occurrence and development of RCC is a multi-step, complex and complex process involving multiple environmental factors, genetic factors and the synergy between genetic factors and environmental factors [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…It is of great interest for us to investigate whether IL-16 rs11556218 can serve as practical biomarkers for these types of cancer in Taiwan. As for IL-16 rs4778889, it has been found that the C allele of IL-16 rs4778889 is associated with the risk of renal cell carcinoma (25), especially among Asian ethnicities (26); however, this polymorphic site is not a contributor to oral cancer risk prediction.…”
Section: Discussionmentioning
confidence: 99%
“…The genotype of IL-16 rs4778889 was found to be associated with the risk of renal cell carcinoma (42). In the most updated meta-analysis of IL-16 genotype and cancer, the C allele at IL-16 rs4778889 was found to significantly correlate with higher renal cell carcinoma risk, especially among Asian ethnicities (43). Different from those findings mentioned above, genotypes of IL-16 rs11556218 were not associated with the risk of the risk of renal cell carcinoma, and the mechanisms need further validation.…”
Section: Discussionmentioning
confidence: 99%